Retraction Note: Novel and efficient process for the synthesis of 1,3,4 Oxadiazole containing MBX-4132 - Ramteke, Prachi; Gill, Manjinder Singh (SynOpen)
The authors wish to retract this article which had been published online on 04 Dec 2024 in error. This was due to unintentional communication errors and the article should have been withdrawn before publication. Any inconvenience is duly regretted.